Diabetic ketoacidosis in children and youth. (November 2012) - Daneman, Denis; Nakhla, Meranda Michel
SUMMARY  Diabetic ketoacidosis (DKA) remains a common complication of Type 1 diabetes, both at the time of diagnosis of the disorder and in those with established diabetes. DKA results from profound insulin deficiency producing hyperglycemia, osmotic diuresis and ketogenesis, eventually leading to dehydration and metabolic acidosis. Provided here is a review of the approach to treatment and prevention of DKA and its complications.